2022
DOI: 10.1186/s12905-022-01597-1
|View full text |Cite
|
Sign up to set email alerts
|

The miscarriage circle of care: towards leveraging online spaces for social support

Abstract: Background Lack of social support during and after miscarriage can greatly affect mental wellbeing. With miscarriages being a common experience, there remains a discrepancy in the social support received after a pregnancy is lost. Method 42 people who had experienced at least one miscarriage took part in an Asynchronous Remote Community (ARC) study. The study involved 16 activities (discussions, creative tasks, and surveys) in two closed, secret Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…It was also reported that women who have experienced a miscarriage rely on two main networks for support: formal (healthcare providers) and informal (friends, family, and work colleagues). The formal care network was seen as the most trusted source of information while the informal network was the main source of tangible support [ 29 ]. The latter represented the larger percentage of reported network of support by the participants in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that women who have experienced a miscarriage rely on two main networks for support: formal (healthcare providers) and informal (friends, family, and work colleagues). The formal care network was seen as the most trusted source of information while the informal network was the main source of tangible support [ 29 ]. The latter represented the larger percentage of reported network of support by the participants in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that seeking both formal and informal help after a miscarriage reduces post-miscarriage health issues [ 30 , 31 ]. Studies by Séjourné et al and Alqassim et al reported significant improvement in health outcomes among women who received various forms of support and help following a miscarriage, including peer counseling, informal social support, and medical consultation [ 30 , 31 ]. The results of the present study were consistent with these findings, as seeking help after a miscarriage was associated with a 3.0% decrease in the prevalence of post-miscarriage health problems.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the chisquare analysis indicated that seeking help was associated with education, place of residence, marital status, distance to a health facility, and access to funds for treatment. Previous research found that seeking both formal and informal help after a miscarriage reduces post-miscarriage health issues [30,31]. Studies by Se ´journe ´et al and Alqassim et al reported significant improvement in health outcomes among women who received various forms of support and help following a miscarriage, including peer counseling, informal social support, and medical consultation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…An increasingly common format for providing psychosocial support and health information is through eHealth or digital health, with the number of users accessing the internet for health services more than doubling in the last decade in Australia (26). Research has shown that people affected by miscarriage often seek information and support online when faced with a lack of support or insufficient information at the time of miscarriage as it is anonymous, easy to access and fills a gap in support needs (27)(28)(29)(30). Our research group has found that individuals often struggle to find a singular reputable Australian based miscarriage website that is accessible, comprehensive, evidence-based and informed by miscarriage experts and healthcare providers (11,30,31).…”
Section: Introductionmentioning
confidence: 99%